Phytochemical profiling, in vitro and in vivo xanthine oxidase inhibition and antihyperuricemic activity of Christia vespertilionis leaf - Endrini, Susi; Abu Bakar, Fazleen Izzany; Abu Bakar, Mohd Fadzelly; Abdullah, Norazlin; Marsiati, Himmi (Elsevier, 2023)
Hyperuricemia happens when excessive levels or under-excretion of uric acid in the blood and is the underlying cause of gout. There are available synthetic drugs that are commonly used to treat gout; however, because of the undesirable side effects, new generations of natural medications with low/no side effects should be explored. The current project was designed to determine the phytochemical profiling, in vitro and in vivo xanthine inhibition and antihyperuricemic activity of Christia vespertilionis leaf aqueous infusion (to mimic human consumption). Profiling of phytochemical was done by liquid chromatography-mass spectrometry (LC-MS). In vitro xanthine oxidase inhibition assay and oxonate-induced hyperuricemia in rats, which are considered as a hallmark for promising antihyperuricemic agents were also conducted. Results showed that phenolics, especially isoferulic acid is the most abundant found in C. verspertilionis aqueous extract based on LC-MS analysis. In vitro xanthine oxidase inhibition assay results also showed that C. verspertilionis aqueous extract display 63.67% inhibition at 100 μg/mL with IC50 value of 61.37 μg/mL. No toxicity was observed after the consumption of C. vespertilionis infusion through in vivo study and C. verspertilionis extract at concentration of 200 mg/kg in rats induced reduction of uric acid in experimental rats by 31.95%. The liver xanthine oxidase activity was also significantly reduced by C. verspertilionis aqueous extract at the same dosage. In conclusion, it is apparent that aqueous infusion of C. verspertilionis might beneficial as an antihyperuricemic agent.